PEMBANGUNAN DESA MANDIRI DAN BERKELANJUTAN MELALUI PENERAPAN EKONOMI HIJAU DI DESA SEKONGKANG BAWAH KECAMATAN SEKONGKANG KABUPATEN SUMBAWA BARAT - Harsono, Iwan; Aryambau, I Komang Dodhy Samasta; Paizir, Muhammad; Hartati, Ola Afria; Setiani, Difika Hari; Summiarni, Summiarni; Sari, Intan Gemala; Raskia, Qikin; Muhayadi, Alifiyan Rizki Naufal; Maulidia, Riska; Effendi, Muhamad Hafid; Harsono, Iwan` (Jurnal Wicara, 2024)
Sekongkang Bawah Village, located in Sekongkang District, West Sumbawa Regency, has abundant natural resource potential, especially in the agricultural sector with main commodities such as corn, watermelon, banana, sweet potatoes, cassava and rice. However, price fluctuations and declines in harvest prices often harm farmers. This research aims to apply the concept of green economy to increase the economic value of agricultural products, especially banana, sweet potatoes, and cassava through the Kuliah Kerja Nyata (KKN) program by University of Mataram students. This program includes training in making processed banana, sweet potatoes, and cassava products, packaging techniques, and marketing strategies. With field survey and interview methods, this activity is expected to improve the welfare of the people of Sekongkang Bawah Village, create new jobs, and support sustainable village development.